Structural and Magnetic Characteristics Evaluation of Iron Oxide Extracted from Printer Toner Wastes - Rodziah, Nazlan; Yuen, Mei Lian; Ros Azlinawati, Ramli (Trans Tech Publications Ltd, Switzerland, 2022)
The need to recycle and develop valuable materials from wastes, and use them in various applications have become increasingly important in recent decades. Printer toner waste is one of the most polluting electronic wastes due to the toxic nature of the material content inside it. Despite the toxicity of the material in the toner powder, it contains iron oxide that can be extracted and recycled to make a beneficial material. Therefore, this study aims to investigate a facile and effective method to extract iron oxide from printer toner waste powder. Magnetic separation and oxidation processes were used as a method for extraction and phase conversion. The structural transformation was investigated using X-ray diffraction (XRD), microstructural observation using scanning electron microscope whereas static magnetic characteristics were investigated using vibrating sample magnetometer. The results from XRD spectra showed that printer toner wastes that have been subjected to magnetic separation process and chemical treatment, even without any heat treatment process, have produced a single-phase magnetite. Through the process of heat treatment on the sample, phase transformation from magnetite to hematite occurred, in which a single phase of hematite is obtained at a temperature of 1400 °C. The saturation magnetization of the sample also showed a reduction where the sample before undergoing the heat treatment process had a saturation magnetization value of 18.81 emu/g but after the heat treatment, the saturation magnetization value decreased to 0.42 emu/g. These results are in line with the phase transformation shown where magnetite has high ferrimagnetic characteristics, whereas hematite is basically antiferromagnetic at room temperature. However, the saturation magnetization that has been obtained in hematite shows a little difference to that of commercially sold hematite. This proves that iron oxide extracted from the printer toner waste has high potential as an alternative to commercial iron oxide available in producing high-performance magnetic materials.